TROPICAL ATLANTIC SST HISTORY INFERRED FROM CA ISOTOPE THERMOMETRY OVER THE LAST 140KA - Hippler D.; Eisenhauer A.; N?gler T.F. (My University, 2006)
Exploring the potentials of new methods in palaeothermometry is essential to improve our understanding of past climate change. Here, we present a refinement of the published ?44/40Ca- temperature calibration investigating modern specimens of planktonic foraminifera Globigerinoides sacculifer and apply this to sea surface temperature (SST) reconstructions over the last two glacial-interglacial cycles. Reproduced measurements of modern G. sacculifer collected from surface waters describe a linear relationship for the investigated temperature range (19.0-28.5 °C): ?44/40Ca [?] = 0.22 (?0.05)*SST [°C] -4.88. Thus a change of ?44/40Ca[?] of 0.22 (?0.05) corresponds to a relative change of 1 °C. The refined ?44/40 Camodern-calibration allows the determination of both relative temperature changes and absolute temperatures in the past. This ?44/40Camodern-calibration for G. sacculifer has been applied to the tropical East Atlantic sediment core GeoB1112 for which other SST proxy data are available. Comparison of the different data sets gives no indication for significant secondary overprinting of the ?44/40Ca signal. Long-term trends in reconstructed SST correlate strongly with temperature records derived from oxygen isotopes and Mg/Ca ratios supporting the methods validity. The observed change of SST of approximately 3 °C at the Holocene-last glacial maximum transition reveals additional evidence for the important role of the tropical Atlantic in triggering global climate change, based on a new independent palaeothermometer. ? 2005 Elsevier Inc. All rights reserved.
Keywords: CALCIUM; HOLOCENE; LAST GLACIAL MAXIMUM; PALEOCEANOGRAPHY; PALEOTEMPERATURE; PLANKTONIC FORAMINIFERA; SEA SURFACE TEMPERATURE; GLOBIGERINOIDES SACCULIFER; Кайнозой::Четвертичная::Голоцен; Cenozoic::Quaternary::Holocene